2019
DOI: 10.2196/10171
|View full text |Cite
|
Sign up to set email alerts
|

Leading by Example: Web-Based Sexual Health Influencers Among Men Who Have Sex With Men Have Higher HIV and Syphilis Testing Rates in China

Abstract: BackgroundThe spread of healthy behaviors through social networks may be accelerated by influential individuals. Previous studies have used lay health influencers to prevent sexually transmitted infections (STIs) among internet-using men who have sex with men (MSM). However, there is a lack of understanding of the characteristics of this key subset of MSM.ObjectiveThis study aimed to examine sociodemographic characteristics, HIV and syphilis testing, and sexual behaviors of Web-based MSM sexual health influenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…; these leaders are commonly referred to as influencers , or a user on social media who has established credibility in a specific industry, has access to a large audience, and can persuade others by virtue of their authenticity and reach (Glucksman, 2017). Influencers’ impact occurs in domains including healthcare (Murphy, 2016), education (Shen et al, 2017), business (Lim et al, 2017), fashion marketing (Cunningham, 2018), and sexual behaviors (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…; these leaders are commonly referred to as influencers , or a user on social media who has established credibility in a specific industry, has access to a large audience, and can persuade others by virtue of their authenticity and reach (Glucksman, 2017). Influencers’ impact occurs in domains including healthcare (Murphy, 2016), education (Shen et al, 2017), business (Lim et al, 2017), fashion marketing (Cunningham, 2018), and sexual behaviors (Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While PrEP campaigns in China have to-date failed to engage relevant communities (60), initiatives in other settings have successfully used MSM-tailored approaches to promote PrEP (3538), including using mHealth technologies to approach GBMSM “where they are “. In an online survey of 1,035 Chinese GBMSM in 2017, about 75% of the participants mainly met their sex partners online (61), and Chinese GBMSM have been using the Internet frequently to search for HIV-related information, counseling or testing services (32). A large body of evidence has suggested that HIV-related and sexual health interventions delivered through Internet-enabled platforms are feasible and acceptable in Chinese settings (62), including interventions through websites, text message and mobile apps that have shown effectiveness in reducing HIV-related risk behaviors, increasing linkage to care, and improving medication adherence (3,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Social marketing enables effective educational programs to be developed based on scientific knowledge and good communication [25]. To be reactive when faced with evolving preferences, it is advisable to design an interconnection of different media sources (eg, websites, apps, social network sites) and to offer attractive components (eg, games, individual spaces, forum discussions, or contact with influencers [26]). Important factors include the structure of the campaign and the content of the message (imaginative, fun, accessible, noninstitutionalized brand image, and engaging) [27].…”
Section: Understanding Online Uses and Risks To Take Advantage Of The Internetmentioning
confidence: 99%